INDUCED MATURATION AND SPAWNING OF INDIAN PENAEID PRAWNS - Muthu, M S; Laxminarayana, A (Indian Journal of Fisheries, 2011)
Penaeid prawn hatcheries are being established in many parts of the world 10 meet the great demand for quality prawn seed for coastal aquaoulture. A steady supply of spawners is essential for efficient programming of the hatchery operations. As the collection of spawners from the sea is a costly and uncertain operation, efforts have been made to induce the captive broodstock to mature under controlled conditions